INDONESIAN FINTECH: BUSINESS ECOSYSTEM AND REGULATION - Sugeng Sugeng; Clara Ignatia Tobing; Rona Fajarwati (Diponegoro Law Review, 2020)
This article will examine the development of the business ecosystem and regulation of Financial Technology (Fintech) in Indonesia, especially lending through electronic transactions, or peer to peer lending (P2P Lending). Although the Financial Services Authority (OJK) has closed the company's activities, but in a short time other illegal companies have emerged, even in larger numbers. This research uses the doctrinal method with the statutory approach. Secondary data is used to explain of legal and social phenomena related to the research topic.The Fintech industry requires specific provisions governing criminal offenses related to Illegal companies.